A LACANIAN ETHICAL RECONSTRUCTION OF SUSTAINABLE AI EDUCATION: Received: 08th December 2025, Revised: 15th December 2025, 16th December 2025, Accepted: 18th December 2025, Date of Publication: 01st January 2026 - Yi Wang, (PEOPLE: International Journal of Social Sciences, 2026)
Within the global agenda of "Sustainable AI and Education," mainstream AI educational systems are predominantly built upon cognitive and behaviorist paradigms. These systems emphasize efficiency, predictability, and immediate feedback, presupposing the learner as a quantifiable and optimizable cognitive subject. However, this technological imagination of a "transparent subject" obscures the fundamental condition of subjective existence revealed by psychoanalysis as early as the beginning of the 20th century—namely, split subjectivity, the insatiability of desire, and the continuous illusion of unconscious processes from structures of meaning. Adopting a Lacanian critical perspective, this paper argues that current AI educational systems, in their attempt to algorithmically satisfy learners' "demands," systematically repress "desire," which constitutes the core dynamism of subjectivity. Lacan emphasizes that the essence of human desire is an eternal pursuit of "lack," rather than a "need" waiting to be fulfilled. When existing AI educational systems operate on learners merely through a cyclical "satisfaction-feedback" pathway, they effectively induce a narcissistic loop akin to the "Imaginary order." This process deprives learners of the opportunity to confront the traumas, unknowns, or gaps of meaning associated with the "Real," thereby obstructing the potential for "symptoms" manifest in the learning process—such as frustration, dissonance, and confusion—to be transformed into creative forces. Based on this analysis, this paper introduces the Lacanian concept of "desire" as a critical entry point for examining the numerous ethical controversies in sustainable AI education. It proposes an ethics of desire for educational practice, positing that AI should not be viewed merely as a technical tool for addressing learners' demands. Instead, it should precisely function as an "Otherness" ethical medium that reveals the structural lack within the subject and guides learners into a dialogue with their own desire. Thus, as an "irreducible heterogeneity" for the learner—that is, an ethical other in the Lacanian sense—AI education can persistently evoke the learner's awareness of the fundamental (lack) inherent in knowledge and the self. This transforms education from an object of technical optimization into a sustainable ethical practice of desire. Within this practice, AI ceases to be a technological tool for narcissistic collusion with the learner and becomes an ethical partner that facilitates the learning subject's continuous transcendence of established cognitive boundaries towards unknown possibilities through the endless dialectic of desire.